Block Liposomes: Vesicles of Charged Lipids with Distinctly Shaped Nanoscale Sphere-, Pear-, Tube-, or Rod-Segments - Zidovska, Alexandra (Methods Enzymol, 2009)
We describe the preparation and characterization of block liposomes, a new class of liquid vesicles, from mixtures of the highly charged (+16 e) multivalent cationic lipid MVLBG2 and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC). Block liposomes (BLs) consist of distinct spherical, tubular, and micellar liposomes which remain connected, forming a single liposome. This is in contrast to typical vesicle systems, where distinctly shaped liposomes are macroscopically separated. In a narrow composition range (8-10 mol % MVLBG2), an abundance of micrometer-scale BLs (typically sphere-tube-sphere triblocks) was observed. Cryo-TEM revealed that BLs are also present at the nanometer scale, where the blocks consist of distinctly shaped nanoscale spheres, pears, tubes, or rods. Pear-tube diblock and pear-tube-pear triblock liposomes contain nanotubes with inner lumen diameter 10-50 nm. In addition, sphere-rod diblock liposomes are present, containing rigid micellar nanorods ≈4 nm in diameter and several μm in length. Block liposomes may find a range of applications in chemical and nucleic acid delivery and as building blocks in the design of templates for hierarchical structures.